Intercultural competencies and lifelong learning of teachers in the Republic of Croatia - Mandarić, Blaženka Valentina (Bogoslovni vestnik, 2023)
The starting point of this article is the complex European socio-cultural context, in which different cultures, customs, religions and worldviews meet but also clash. All of that extends into the educational environment, which is now facing intense challenges of multiculturalism. Schools are expected to enable students to live in a multicultural society, and that process includes the acquisition of intercultural competencies. In order for schools to successfully achieve this educational goal, they need to have quality teachers. In addition to basic education, teachers participate in continuing education – i.e. lifelong learning. The article analyses and evaluates the correlation between intercultural competencies and lifelong learning of teachers in the Republic of Croatia. The first chapter discusses the intercultural competences of teachers as a European strategic educational goal within international qualifications. The second part explores, relying on the European guidelines and recommendations of the National Council for Education, the lifelong learning of teachers in the Republic of Croatia, which includes learning for the development of intercultural competencies. The third part is dedicated to the critical evaluation of intercultural competencies of religious education teachers with regard to initial education programmes and professional development programmes in the Republic of Croatia.
Keywords: formacija učiteljev verske vzgoje; formation of religious education teachers; interculturalism; kompetence učiteljev; lifelong learning; medkulturnost; okvir kvalifikacij; qualifications framework; teacher competencies; vseživljenjsko učenje